Nonparametric Instrumental Variable Estimation of Structural Quantile Effects - V., Chernozhukov,; P., Gagliardini,; Scaillet, Olivier (Econometrica, 2012)
We study the asymptotic distribution of Tikhonov Regularized estimation of quantile structural effects implied by a nonseparable model. The nonparametric instrumental variable estimator is based on a minimum distance principle. We show that the minimum distance problem without regularization is locally ill-posed, and consider penalization by the norms of the parameter and its derivatives. We derive pointwise asymptotic normality and develop a consistent estimator of the asymptotic variance. We study the small sample properties via simulation results, and provice an empirical illustration to estimation of nonlinear pricing curves for telecommunications services in the U.S.